(untitled) (Tazakka: Jurnal Pendidikan dan Keislaman, 2024)
This research was motivated by the Minsai Alfitrah Pencak Silat College where pencak silat activities do not only teach martial arts moves or knowledge. Each exercise has a process to start the exercise to see the character of the students from the start of the exercise to the end of the training process. This research aims to describe teaching character values ​​through Minsai Alfitrah Pencak Silat movements, describe growing character awareness through Minsai Alfitrah Pencak Silat training and describe the Minsai Alfitrah Pencak Silat school in controlling and supervising the behavior or character of Pencak Silat students. This research was designed using qualitative research, in this case, the type of research used was a case study with data collection by using interviews, observation and documentation. The analyz data used is data reduction, data display and conclusions. The results of this research show that there are 5 strengthening character education values ​​through Minsai Alfitrah Pencak Silat at the Al-Zamriyah Payakumbuh Islamic Boarding School, growing character awareness through the Minsai Alfitrah Pencak Silat extracurricular at the Al-Zamriyah Payakumbuh Islamic Boarding School including methods: 1) method of providing examples good, 2) habituation method, 3) punishment method.